PENGARUH SENAM LANSIA TERHADAP PENURUNAN TEKANAN DARAH PADA LANSIA PENDERITA HIPERTENSI DI DESA JOSARI KECAMATAN JETIS KABUPATEN PONOROGO - Ria Fajar Nurhastuti (AKADEMI KEBIDANAN HARAPAN MULYA PONOROGO, 2022)
Blood Pressure in elderly will change with age, in general after entering the age of 45 years the condition of the arterial wall will be thickened by several factors such as the accumulation of collagen substances in the muscle layer, so that it can cause blood vessels to narrow gradually. Elderly gymnastics is a mild and non-stressful exercise proven to help improve physical and mental health for the elderly. The purpose of this study was to determine the effect of elderly gymnastics on reducing blood pressure in the elderly who experience hypertension in Josari Village, Jetis District, Ponorogo Regency. The design used in this study was to use a